Outcomes and the effect of PGT-M in women with hormone-related hereditary tumor syndrome - Wang, Dingran; Song, Xueling; Zhu, Xiaohui; Yan, Liying; Zhi, Xu; Yan, Jie; Liang, Huamao; Qiao, Jie (Frontiers in Oncology, 2024)
To review the outcome of PGT-M in hormone-related hereditary tumor syndrome and evaluate the effect of ovarian induction on tumor growth in those patients.Medical records of PGT-M were retrospectively analyzed in patients with hormone-related heritage tumors in our reproductive center. A total of eleven women with hereditary breast and ovarian cancer (HBOC) (including BRCA1/2 mutation carriers), and Lynch syndrome (including MMR gene mutation carriers) were included. Thirteen IVF/PGT-M cycles were performed. Eleven for PGT-M and two for fertility preservation. The ovulation protocol, numbers of oocytes retrieved and two pronuclei (2PN) zygotes, PGT-M results, and clinical outcomes were analyzed. Tumor progression was also estimated by comparing transvaginal ultrasound (TVS), MR, CT, or colonoscopy according to the follow-up requirements of different tumors.Eleven IVF/PGT-M cycles were performed with an antagonist protocol; Two cycles were performed with a mild stimulation protocol. The total dose of gonadotropin (Gn) was 1827 IU per patient (range from 1200 to 2625 IU). The median number of oocytes retrieved was 13 (range from 4 to 30), and the median number of 2PN zygotes was 8 (range from 2 to 16). A total of 32 embryos underwent PGT-M, and 9 (28.1%) embryos were suitable for transfer. Six transfer cycles were performed, and 5 cycles got clinical pregnancy (83%) with five newborns (83%). The follow-up examinations conducted 10-18 months after PGT-M/delivery revealed no new lesions or tumor progression.PGT-M results can provide important information for improving the consultation of hormonerelated heritage tumor patients regarding their fertility preservation and reproductive options. Ovarian induction for women with hormone-related hereditary tumor syndrome is not associated with tumor progression.